2014
DOI: 10.15288/jsad.2014.75.124
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Responses to Alcohol in the Lab Predict Neural Responses to Alcohol Cues

Abstract: ABSTRACT. Objective: Subjective responses to alcohol represent a biologically based, genetically moderated, and clinically informative marker of alcoholism risk; however, the physiology underlying this phenotype remains unclear. This study tested whether subjective responses during alcohol administration predict neural responses to alcohol cues in the scanner and whether these neural responses differ between OPRM1 genotypes. Method: Twenty alcohol-dependent individuals were recruited (10 G-allele carriers; 6 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…It is possible that the 3-day dosing duration was not long enough for naltrexone to establish its full opioid blockade effect; thus the duration of dosing could potentially explain the absence of naltrexone-induced modulations of ventral striatum activation (and VTA activation at the whole-brain level of analysis) and measures of self-reported craving in the present study. However, the absence of naltrexone-related reductions in self-reported craving may also be related to the craving assessment procedure used (ie, phasic measurement of craving with a single item during scanning) as other studies have observed a benefit of using expanded item and response sets for the detection of drug craving correlations with neural measures of cue-reactivity (Courtney and Ray, 2014b). Further, previous studies have demonstrated complete hydromorphone blockade following a single dose of naltrexone (25 or 100 mg; Preston and Bigelow, 1993;Schuh et al, 1999) and others have observed reductions in alcohol and drug craving following 3-day dosing of naltrexone (Ray and Hutchison, 2007), suggesting that the measurement limitation theory may be a more viable explanation for the lack of naltrexone-related tonic craving reductions observed in the present study.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…It is possible that the 3-day dosing duration was not long enough for naltrexone to establish its full opioid blockade effect; thus the duration of dosing could potentially explain the absence of naltrexone-induced modulations of ventral striatum activation (and VTA activation at the whole-brain level of analysis) and measures of self-reported craving in the present study. However, the absence of naltrexone-related reductions in self-reported craving may also be related to the craving assessment procedure used (ie, phasic measurement of craving with a single item during scanning) as other studies have observed a benefit of using expanded item and response sets for the detection of drug craving correlations with neural measures of cue-reactivity (Courtney and Ray, 2014b). Further, previous studies have demonstrated complete hydromorphone blockade following a single dose of naltrexone (25 or 100 mg; Preston and Bigelow, 1993;Schuh et al, 1999) and others have observed reductions in alcohol and drug craving following 3-day dosing of naltrexone (Ray and Hutchison, 2007), suggesting that the measurement limitation theory may be a more viable explanation for the lack of naltrexone-related tonic craving reductions observed in the present study.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…Exposure to substance-related cues and environments has also been found to be related to changes in alcohol consumption (Monk et al 2015 ), as well as related cognitions (Monk and Heim 2013a , b , 2014 ), relapse (e.g. Carter and Tiffany 1999 ; Marlatt 1990 ; Siegel 2005 ; Zironi et al 2006 ) and craving (Conklin and Tiffany 2002 ; Courtney and Ray 2014 ; Modell and Mountz 1995 ).…”
mentioning
confidence: 99%
“…Considering that the Craving criterion was not included in the three studies above-cited (Kuerbis et al, 2013;McBride et al, 2011;Shmulewitz et al, 2010) our study was the second to validate the inclusion of this criterion within the DSM-5 AUD, in a non-U.S. large representative sample, and the first in a middle-income country. As stated by some authors (Keyes et al, 2011;Pombo et al, 2014;Courtney and Ray, 2014;Leggio, 2009), the support for the validity of craving as a component of alcohol addiction also comes from other research fields such as behavioral research, imaging, pharmacology, and genetic epidemiology.…”
Section: Discussionmentioning
confidence: 97%